FACELIFT AND POST-FACELIFT REHABILITATION - Mehmet Mustafa Besirikli (Scholar Express Journals, 2025)
In modern aesthetic medicine, facelift occupies a special place among plastic surgeries, demonstrating a steady increase in popularity in recent decades. The desire to preserve youth and attractiveness, the increasing influence of social standards of beauty, as well as the development of innovative surgical techniques contribute to an increase in the number of facial rejuvenation operations
Keywords: Facelift; face lifting; rehabilitation period